Scattering of image-potential-state electrons by steps on Cu(001) - Fauster, Thomas; Schneider, M. Alexander; et al. (Applied Physics A-Materials Science & Processing, 2004)
Scanning tunneling spectroscopy (STS) reveals a distinct asymmetry in the scattering properties of an isolated step for the n=1 image-potential state on Cu(001). The elastic scattering probability for an electron traveling downstairs is determined from the strength of density oscillations in front of a step edge and is found to be approximately two times higher than for the opposite upstairs direction. A one-dimensional scattering model is extended to the case of asymmetric transmission and reflection coefficients. The calculations using the asymmetry measured by STS explain the dispersion and the decay rate of the n=1 band on Cu(119) measured by two-photon photoemission. In particular, the asymmetry of the decay rate can be described quantitatively with a minimum of adjustable parameters. While the results can also be transferred successfully to the Cu(1115) surface, the limit of applicability is reached for Cu(117) with a step separation of 3.5 nearest-neighbor distances.